PENGARUH PENGGUNAAN TIPE MAKE A MATCH TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA DI SEKOLAH DASAR - Sumiyati, Sumiyati; Marli, Suhardi; Margiati, K Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the influence of Make a Matchtype for student learning results in grade V of Elementary School 09 East Pontianak. The method used is the experimental method. This research, using Quasi Experimental design with form Nonequivalent Control Group Design.The research sample in this study is the all grade V student. The data collecting technique is a measurement technique. The data collection tool used is a test. Based on the data analysis, the result of average post-test of experimental class is 76,22 and post-test of control class is 68,17, tcount2,157 and ttable(? = 5% and dk = 25 + 24 - 2 = 47) of 1,994, because tcount>ttable, then Ha accepted. So, it can be concluded that there is the influence of Makea Matchtype for student learning results. The effect size calculation obtained ES = 0,63 which pertained in height, that is ES > 0,8. It can be said that Make a Matchtypegives a high influence on the learning result of Social Sciences in theV grade of Elementary School 09 East Pontianak.Keywords:Make a Match, Learning Outcomes Of Students,Social Sciences